Firm Productivity and Locational Choice : Evidence from Mozambique - Iimi, Atsushi (World Bank, Washington, DC, 2021)
Transport infrastructure is an important driving force for economic growth. Africa has been lagging behind in the global manufacturing market. Among others, infrastructure is often an important constraint. The paper reexamines the impacts of transport infrastructure on firm productivity in Mozambique. A conventional cost function is estimated with two rounds of firm data collected in 2007 and 2018. It is found that improved transport connectivity, particularly access to a port, has a positive impact on firm production. Firm inventory is also an important determinant of firm productivity. Over the long term, agglomeration economies are also found to be significant and associated with port accessibility. These findings are consistent with the fact that the Government of Mozambique heavily invested in the primary road network during the first half of the 2010s. The improved transport network is considered to have contributed to the country’s robust economic growth in the industrial and service sectors until the mid-2010s.